Highly efficient three-phase grid-connected parallel inverter system - Isen, Evren; Bakan, Ahmet Faruk (SPRINGEROPEN, 2018)
In this paper, a new three-phase grid-connected inverter system is proposed. The proposed system includes two inverters. The main inverter, which operates at a low switching frequency, transfers active power to the grid. The auxiliary inverter processes a very low power to compensate for the grid current ripple. Thus, no active power is processed by the auxiliary inverter. The goal is to produce a grid current with a low total harmonic distortion (THD) and to obtain the highest efficiency from the inverter system. The main inverter is controlled via a space-vector pulse-width modulation owing to its optimum switching pattern, and the auxiliary inverter is controlled via a hysteresis current-control technique owing to the technique's fast dynamic response. The proposed system is analyzed in terms of different DC-link voltage, switching frequency, and filter inductance values. The optimum system parameters are selected that provide a THD value of less than 5%. A prototype inverter system at a 10-kW output power has been implemented. The main inverter operates at a 3-kHz switching frequency, and the auxiliary inverter compensates for the grid-current ripple. In total, a THD of 4.33% and an efficiency of 97.86% are obtained using the proposed inverter system prototype.
Keywords: Active filter; Inverter efficiency; Ripple cancellation; Three-phase grid-connected inverter; CURRENT CONTROLLER; CONTROL SCHEME; NPC INVERTER; FILTER; DESIGN; Engineering